Laparoscopic treatment of vesicouterine fistula (a literature review and case report) - Denis P. Kholtobin; Aziz O. Nabiev; Sergey A. Nekludov; Ekaterina V. Kulchavenya (IP Berlin A.V., 2021)
Urogenital fistulas are common complication of obstetric and gynecological surgery; the most common are vesicovaginal fistulas. Vesicouterine fistulas are rare, which explains the difficulties in diagnosis and treatment. The literature review and own clinical case presented in article. A 43-years-old female patient was consulted with complaint of urinary leakage from vagina, which appeared 1 month after the cesarean section and vesicouterine fistula has been diagnosed. Successful laparoscopic treatment of vesicouterine fistula was performed at the Avicenna Medical Center after 3 months. The urethral catheter was removed 7 days after surgery. At control examination after 1, 3 and 6 months, ultrasound examination of the pelvic organs confirmed the consistency of the scar on the uterus. Urination remained free and painless, the patient did not notice urine leakage. This clinical observation shows the possibility of treating a vesicouterine fistula with a laparoscopic approach with a good result and the possibility of early rehabilitation.